ZONASI DAN STATUS KAWASAN EKOSISTEM LAGUNA DI NEGERI IHAMAHU, MALUKU TENGAH - Louhenapessy, Daniel (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2019)
Lagoon ecosystems have high productivity in the fisheries sector. Communities of Ihamahu village utilize resources in this ecosystem to meet their daily needs. The aim of this study was to analyze the zoning map and the status of the lagoon ecosystem of Ihamahu village. The research method used in this research was the Geogrpahic Information System with using spatial analysis techniques in collaboration with the Focus Group Discussion (FGD) method. The results revealed that there were nine lagoons with different areas. Four out of nine lagoons are used as conservation, aquaculture, fishing and rehabilitation sites. The establishment of the zonation and status of lagoon areas is a proper way to manage the lagoon ecosystem sustainably. ABSTRAK Ekosistem laguna memiliki produktivitas yang tinggi dalam sektor perikanan. Masyarakat Negeri Ihamahu memanfaatkan sumberdaya pada ekosistem laguna untuk pemenuhan kebutuhan hidup. Tujuan penelitian ini adalah menganalisis peta zonasi dan status kawasan ekosistem laguna Negeri Ihamahu. Metode penelitian yang digunakan untuk menganalisis peta zonasi dan status kawasan yaitu dengan pendekatan SIG melalui teknik analisis spasial serta metode Focus Group Discussion (FGD). Hasil penelitian menunjukkan terdapat sembilan laguna dengan luasan yang berbeda. Berdasarkan hasil FGD diperoleh empat status kawasan ekosistem laguna Negeri Ihamahu yaitu kawasan konservasi, budidaya, penangkapan serta rehabilitasi. Penetapan zonasi dan status kawasan merupakan upaya pengelolaan ekosistem laguna secara berkelanjutan. Kata Kunci: laguna, pengelolaan berkelanjutan, SIG, konservasi, rehabilitasi